2005
DOI: 10.1021/jf051264d
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Compounds from the Outer Scales of Onion

Abstract: Antioxidative compounds were isolated from the methanol extract of dry outer scales of onion (Allium cepa L.). Nine phenolic compounds (1 − 9) were finally obtained by reversed-phase high-performance liquid chromatography, and their structures were elucidated by NMR and mass spectrometry analyses. They were the six known compounds, protocatechuic acid (1), 2-(3,4-dihydroxybenzoyl)-2,4,6-trihydroxy-3(2H)-benzofuranone (2), quercetin 4‘-O-β-d-glucopyranoside (3), quercetin (5), 4‘-O-β-d-glucopyranoside of querce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
139
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(160 citation statements)
references
References 26 publications
(52 reference statements)
16
139
0
3
Order By: Relevance
“…5) in accordance with previously reported data (LY et al, 2005). In a similar fashion, compound (9) was identifi ed as a quercetin dimer (LY et al, 2005;GÜLŞEN et al, 2007a). Compounds (1) and (9) have been demonstrated to derive from quercetin through oxidative cleavage by onion peroxidase (OSMAN et al, 2008).…”
Section: Polyphenolic Compositionsupporting
confidence: 87%
See 3 more Smart Citations
“…5) in accordance with previously reported data (LY et al, 2005). In a similar fashion, compound (9) was identifi ed as a quercetin dimer (LY et al, 2005;GÜLŞEN et al, 2007a). Compounds (1) and (9) have been demonstrated to derive from quercetin through oxidative cleavage by onion peroxidase (OSMAN et al, 2008).…”
Section: Polyphenolic Compositionsupporting
confidence: 87%
“…These compounds were assigned to adducts of quercetin with quercetin 4´-O-glucoside (Fig. 5) in accordance with previously reported data (LY et al, 2005). In a similar fashion, compound (9) was identifi ed as a quercetin dimer (LY et al, 2005;GÜLŞEN et al, 2007a).…”
Section: Polyphenolic Compositionsupporting
confidence: 85%
See 2 more Smart Citations
“…It is estimated that more than 450,000 tonnes of onion solid waste is produced each year in Europe (Moure et al 2001). The non-edible portions of the onion bulb, which are considered as waste of onion consumption and processing, contain phenolics with very peculiar structures, not encountered in the edible parts (Furusawa et al 2003;Ly et al 2005;Ramos et al 2006). However, recent studies on the recovery of flavonols from onion solid wastes clearly showed that mainly quercetin and to a lesser extent, quercetin glucosides are the major phenolics in onion trimmings and the outer dry layers, and account for strong antioxidant effects (Beesk et al 2010;Khiari et al 2008;Kiassos et al 2009;Suh et al 1999).…”
Section: Introductionmentioning
confidence: 99%